2020
DOI: 10.21203/rs.3.rs-103890/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quaternized carbon quantum dots with broad-spectrum antibacterial activity for treatment of wounds infected with mixed bacteria

Abstract: Quaternized carbon quantum dots (qCQDs) with broad-spectrum antibacterial activity were synthesized by a simple green “one-pot” method using dimethyl diallyl ammonium chloride and glucose as reaction precursors. The qCQDs showed satisfactory antibacterial activity against both gram-positive and gram-negative bacteria. In rat models of wounds infected with mixed bacteria, qCQDs obviously restored the weight of rats, significantly reduced the death of rats from severe infection, and promoted the recovery and hea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Little is known about the molecular mechanism of antibacterial activity once carbon quantum dots have gained intra-cellular access through cell wall damage. It is likely that carbon quantum dots affect gene expression [90].…”
Section: Mechanisms Of Antibacterial Activity Of Carbon Quantum Dotsmentioning
confidence: 99%
See 4 more Smart Citations
“…Little is known about the molecular mechanism of antibacterial activity once carbon quantum dots have gained intra-cellular access through cell wall damage. It is likely that carbon quantum dots affect gene expression [90].…”
Section: Mechanisms Of Antibacterial Activity Of Carbon Quantum Dotsmentioning
confidence: 99%
“…Quaternized carbon quantum dots prepared from dimethyl diallyl ammonium chloride and glucose as precursors had MIC values between 12.5 µg/mL and 25 µg/mL for Gram-positive S. epidermidis, S. aureus, MRSA and E. faecalis, ranging up to 50 µg/mL for Gram-negative E. coli and P. aeruginosa (also see Table 2) [90]. Proteomic analyses suggested that the quaternized carbon quantum dots acted on ribosomal proteins in Gram-positive bacteria and downregulated metabolization-related proteins of Gram-negative bacteria.…”
Section: Gram-positive Vs Gram-negative Strainsmentioning
confidence: 99%
See 3 more Smart Citations